Predictive value of serum soluble B7‐H4 in acute pancreatitis. (11th August 2020) - Cheng, Zhixiang; Liu, Zhengfang; Yuan, Yufeng; Liu, Zhisu; He, Yueming; Jiang, Ping
Abstract: Background: Studies reported that soluble B7‐H4 (sB7‐H4) was significantly related to the progression and prognosis of inflammatory diseases, and whether sB7‐H4 is related to the severity and prognosis of acute pancreatitis (AP) timely has not been reported. Materials and methods: Clinical database data of 446 AP patients were retrospectively collected, and the correlation between the expression serum levels of sB7‐H4 with inflammatory factors and prognostic scores was analysed in AP patients. Results: Soluble B7‐H4 was significantly correlated with IL‐6, IL‐8, TNF‐α, PCT, CRP levels and WBC count ( P < .01), with correlation coefficients of R = .61, .53, .46, .60, .57 and .47, respectively, and AUCs were 0.905, 0.837, 0.797, 0.858, 0.890, 0.841 and 0.855, respectively. In addition, sB7‐H4 was significantly correlated with the Ranson score, APACHE II score and BISAP score ( P < .001), with correlation coefficients of R = .58, .63 and .59, respectively. The AUCs of assessing local complications of AP were 0.908, 0.863, 0.785 and 0.844, respectively; assessing organ failure were 0.872, 0.790, 0.796 and 0.857, respectively; and assessing in‐hospital mortality were 0.839, 0.821, 0.796 and 0.823, respectively. Conclusions: Soluble B7‐H4 could be used as a marker for the diagnosis, severity assessment and poor prognosis assessment of AP patients, which may have potential clinical applications.